Serosurveys to detect SARS-CoV-2 antibodies among high-risk groups in six urban cities of Odisha, India - Srikanta Kanungo; Sidhartha Giri; Debdutta Bhattacharya; Jaya Singh Kshatri; Subrata Kumar Palo; Debaprasad Parai; Jyotirmayee Turuk; Ira Praharaj; Asit Mansingh; Girish Chandra Dash; Hari Ram Choudhary; Matrujyoti Pattnaik; et al. (Journal of Infection in Developing Countries)
Introduction: Personnel involved in essential services or residing in high-risk areas during the COVID-19 pandemic are at increased risk of getting infected. We evaluated the proportion of personnel infected in several high-risk groups in Odisha using seroprevalence studies.